Pengaruh Harga, Kualitas Layanan Dan E-Promotion Minat Beli Konsumen Shopeefood (Study Kasus Mahasiswa Aktif FEB UNISMA Angkatan 2018) - Moh. Hefni Munawar; Muhammad Agus Salim; Afi Rachmat Slamet (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
AbstractThis research was conducted on the 2018 FEB UNISMA Active Students. The type of research using a quantitative approach is the research used. The purpose of this research is to find out how much the price of something, service quality, e-Promotion on consumer buying interest. The independent variables used are price, service quality, e-promotion, consumer buying interest, which is the dependent variable. The sample of this study consisted of 72 respondents who were consumers aged 19-24 years, Active Students of FEB UNISMA Class of 2018 who had or often made purchases. Using a questionnaire as a data collection tool. With the aid of the computer program SPSS 16.0, the data were analyzed using an instrument test, multiple linear regression analysis, the classical assumption test, the determination test, the f test, and the t test. The findings of this study indicate that pricing has a significant impact on consumer buying interest, service quality has a significant effect on consumer buying interest, e-promotion has a significant effect on consumer buying interest. Price, Service quality, and Consumer Buying Interest are affected by e-Promotion simultaneously. Keywords : Price, Service Quality, e-Promotion, Consumer Buying Interest.